Toward Sustainable Biocultural Ecotourism: An Integrated Spatial Analysis of Cultural and Biodiversity Richness in Colombia - Alejandra Echeverri; Natasha M. Batista; Stacie Wolny; Guido A. Herrera‐R; Federico Andrade‐Rivas; Allison Bailey; Anaid Cardenas‐Navarrete; Armando Dávila Arenas; Andres Felipe Díaz‐Salazar; Katherine Victoria Hernandez; Kelley E. Langhans; Bryam E. Mateus‐Aguilar; et al. (People and Nature, 2025)
Abstract Ecotourism plays a vital role in both economic development and depending on the scale, it can also aid environmental conservation. Ecotourism planning often considers culture‐based and nature‐based tourism separately, failing to recognize the synergies between them, with the potential to market locations as biocultural destinations. Using Colombia as a case study, we created metrics of taxonomic biological diversity as measured by vertebrate species richness (including birds, mammals, freshwater fishes, reptiles and amphibians) and institutionalized cultural richness (by counting the number of UNESCO World Heritage Sites, UNESCO Intangible Cultural Heritage sites, museums, endemic music festivals, Afro‐Colombian Territories and Indigenous Reserves) and evaluated the spatial correlations between them. To determine biocultural ecotourism potential, we evaluated whether biocultural richness was accessible and mapped potential biocultural ecotourism supply. By mapping areas of sports fisheries, birdwatching destinations, national park annual visitors and airport arrivals we also estimated spatial demand. We also analysed the difference between biocultural ecotourism supply and demand to assess the realized and untapped potential for biocultural destinations. While biocultural richness is high in the Amazon, Pacific and Caribbean regions, we found that there are no win‐win‐win locations where culture, species richness and accessibility are all high. Areas with great potential for biocultural ecotourism development largely coincide with designated Indigenous Reserves and Afro‐Colombian Territories. Our paper suggests that Colombia is currently safeguarding its biocultural capital and that it remains inaccessible to tourists. This study underscores the power of integrating cultural and biological variables to reshape the ecotourism sector. Read the free Plain Language Summary for this article on the Journal blog.